Manusia di Era Kebudayaan Digital: Interpretasi Ontologis Martin Heidegger - Oktarizal Drianus (MAWA IZH JURNAL DAKWAH DAN PENGEMBANGAN SOSIAL KEMANUSIAAN, 2018)
The aims of paper is digging beneath the ontological relations between human and technology. It is handled by drawing a inspiration from Martin Heidegger's thought, specifically the period of Heidegger II. This library research discusses two key of Heidegger’s texts against technology, namely: “Questions concerning Technology” and “Discourse about Thinking”. The paper provides some findings: 1) The Dasein reconstruction transforms toward Digi-sein as the only and one Questioner of Being that exist within a heart of digital culture; 2) Heideggerian destruction of gestell as a framed way of thinking that makes humans and technology relations become non-free relations. Heidegger calls calculative thinking as actually "flight from thinking". Gestell shackles us in exploitative ways of thinking that oppose disclosure the veil of human openness to the Being; 3) Heidegger employs gelassenheit as a simple and relaxed attitude, as releasement, that was not impermeable to nuances of metaphysics and religion. Gelassenheit was living an attitude that kept a tension between saying "yes" and "no", simultaneously and ambiguously. Technology is addressed by “let it be” attitude, and release the technology as it is.